Formulasi dan Evaluasi Sediaan Balsam Dari Kombinasi Minyak Atsiri Alpina Galanga dan Ekstrak Kaemferia Galanga: Formulation and Evaluation of a Balm Preparation Containing a Combination of Alpinia galanga Essential Oil and Kaempferia galanga Extract - Jaroh, Assolychathu; Remanti, Etis; firduas, Firdania; Kristijono, Ary (Jurnal Abdi Keperawatan dan Kedokteran, 2026)
The utilization of natural products as alternative therapeutic agents has received growing attention, particularly in the development of topical balm formulations for muscle pain relief. Galangal (Alpinia galanga) and kencur (Kaempferia galanga) are medicinal plants rich in bioactive compounds that may exert therapeutic effects while providing characteristic aromas that enhance user acceptability. This study aimed to formulate a topical balm containing a combination of galangal essential oil and kencur extract and to evaluate the physical quality of the resulting formulations. An experimental laboratory study was conducted by preparing three balm formulations with varying concentrations of galangal essential oil, while the concentration of kencur extract was maintained constant. No human subjects were involved. The evaluated parameters included organoleptic characteristics (color, consistency, and odor), homogeneity, viscosity, spreadability, adhesiveness, and pH. All physical evaluations were performed using standardized laboratory procedures and instruments, including a viscometer, pH meter, and glass plates. The results demonstrated that all formulations produced semi-solid balms with a brownish-white appearance and showed good homogeneity without any phase separation. Significant differences were observed among the formulations in viscosity, spreadability, and adhesiveness. Formulation 3 exhibited the most favorable physical properties, with a viscosity of 26,933 ± 153, spreadability of 5.7 ± 0.10, and adhesiveness of 7.3 ± 0.10. Furthermore, all formulations displayed pH values within the physiological range of human skin, with Formulation 3 showing a pH of 5.9 ± 0.10, which was closest to normal skin conditions. In conclusion, the combination of Alpinia galanga essential oil and Kaempferia galanga extract can be successfully formulated into a stable topical balm that meets essential physical quality requirements. Formulation 3 was identified as the most suitable formulation and demonstrates strong potential for further development as a safe and effective herbal topical product.